Utilization of peripheral glucose and lactate differences in the diagnosis of feline arterial thromboembolism: a multi-center study - Yee, Michael; Guillaumin, Julien; 't Hoen, Meredith; Cai, Jiazhang; Mochel, Jonathan; Walton, Rebecca (Frontiers in Veterinary Science, 2024)
ObjectiveTo establish lactate and glucose differences between affected and non-affected limbs in cats with feline arterial thromboembolism (FATE). To evaluate the correlation between these values and survival to discharge as well as congestive heart failure (CHF).MethodsBlood glucose and lactate concentrations were prospectively obtained on admission from client-owned FATE cats and client-owned cats presented for other conditions. The glucose and lactate concentrations of the front limbs (or non-affected) and the hind limbs (or affected) were measured. Lactate (Δlactate) and glucose (Δglucose) differences between the two limbs were calculated.ResultsThe FATE group and control groups included 18 and 41 cats, respectively. The median age of the cats within the FATE group and control groups was 9.5 years and 5 years, respectively. The median Δlactate was significantly higher in the FATE group than in the control group (7.2 mmol/L versus 0.1 mmol/L, respectively; p ≤ 0.01). The median Δglucose was significantly higher in the FATE group than in the control group (155 mg/dL versus 3 mg/dL, respectively; p ≤ 0.01). A diagnosis of FATE was made using a ∆lactate cutoff of 2.2 mmol/L (100% sensitivity and 95% specificity) or a ∆glucose cutoff of 41 mg/dL (100% sensitivity and specificity). There was no correlation between Δlactate and Δglucose and survival to discharge. A higher ∆glucose was significantly associated with concurrent CHF (p = 0.01).ConclusionBoth Δlactate and Δglucose were accurate diagnostic tools for cats with FATE. Neither were correlated with survival to discharge. Higher Δglucose values were significantly associated with the presence of CHF.